(untitled) (Journal of Geography and Environmental Management, 2021)
In the modern conditions of the development of geospace, the process of the emergence of new and development, the transformation of the classical concepts of settlement is activated. This is primarily due to the initialization of the guiding ideas for the formation of systems for the distribution of the population and productive forces in mono-territories (various state entities). It can be considered as a response to the excessive spatial urbanization of the settlement core (monofunctional centers) and the underdevelopment of elements (small towns, townships or villages), that serve them. The article discloses the preconditions for the formation of settlement systems, considering their mutual ordered spatial distribution of the population and the productive forces of territorial monosystems, identifies their types. Modern concepts of constructing models of settlement systems within the limits of recreational-tourist and agro-industrial territorial monosystems have been analyzed. Practical examples of the application of the concepts of settlement systems based on an ethnic basis, in particular, «Jewish Village», «Italian Village», «Swedish Village», «Chinese Village» and others, as well as examples of thematic concepts of the formation of tourist mono-settlements have been given. At the same time, it has been proven that effective territorial management makes such territories the most successful in the context of a gradual narrowing of the space for the geographical differentiation of human activity (or the deepening of the phenomenon of the geographical division of labor). The research will be of interest to local governments in improving the development of the settlement system and substantiating the prospects for its functioning, activating social activity, and increasing the level and quality of population life, in particular, in rural areas.